Open innovation and crowdsourcing - Randhawa, Krithika (Henry Stewart Talks, 2021)
What open innovation Is, What crowdsourcing is, Process of crowdsourcing, Modes of crowdsourcing, Strategic choices for open innovation and crowdsourcing, Organizing and managing crowdsourcing